A reestruturação dos bancos estaduais pós-PROES: análise do caso BANRISUL - Gutierrez, Cláudio Tito Gutierrez (2008)
This work examines the restructuring of the state banks inserted in the stabilization program of Plano Real. With the crisis in the public funds, in the beginning of the 1980 decade, the states financing device falls apart the states appeal to other financing devices, witch include the state banks. It is an assumption of this work that the crisis in the state financial institutions is due to the combination of the state economic crisis, the lack of legal and perceptive framework, as well as of institutions that might mediate such critical situations. Our analysis disagrees with the prevalent analysis in the period between 1994 and 2002, by which the state banks were inherently inefficient institutions. The crisis in the state banks lasted until there happened the ultimate negotiation of the state banks debts with Plano Real. The Proes witch was a program created with the purpose of restructuring state banks, trough privatization or liquidation of state financial institutions. Our analysis approaches the case of Banrisul, witch is a state bank that underwent a process of restructuring and remained under state control; it is ascertained that the economic and accounting data after restructuring presented evidence of strong financial recovering of the bank, which strengthens the assumptions discussed in this work.